2016
DOI: 10.3390/f7070139
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Local Drivers of Fire Cycle Heterogeneity in Boreal Forests: A Scale Issue

Abstract: Abstract:Severe crown fires are determining disturbances for the composition and structure of boreal forests in North America. Fire cycle (FC) associations with continental climate gradients are well known, but smaller scale controls remain poorly documented. Using a time since fire map (time scale of 300 years), the study aims to assess the relative contributions of local and regional controls on FC and to describe the relationship between FC heterogeneity and vegetation patterns. The study area, located in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Previous studies at local scales in eastern Canada have shown that SDs influence fire cycles (Mansuy et al 2010;Bélisle et al 2016). At our larger scale, LDs dominated by SDs presenting a coarse or medium texture were the most likely to have a nonnull BR, followed by LDs dominated by bedrock, and finally LDs dominated by fine texture SDs or organic deposits.…”
Section: Physical Environmentmentioning
confidence: 68%
See 1 more Smart Citation
“…Previous studies at local scales in eastern Canada have shown that SDs influence fire cycles (Mansuy et al 2010;Bélisle et al 2016). At our larger scale, LDs dominated by SDs presenting a coarse or medium texture were the most likely to have a nonnull BR, followed by LDs dominated by bedrock, and finally LDs dominated by fine texture SDs or organic deposits.…”
Section: Physical Environmentmentioning
confidence: 68%
“…Low hills and hills are mostly found on thick till deposits with coarse or medium textures (Robitaille et al 2015) that facilitate fire spread. In contrast, high hills and mounts are generally found on thin tills and bedrock in rugged landscapes that can act as firebreaks (Bélisle et al 2016). Moreover, high hills and mounts most often have a higher elevation than the other two relief classes.…”
Section: Physical Environmentmentioning
confidence: 96%
“…The region is also characterized by an important variability of surficial deposits, from organic deposits and bedrock to till dominance from south to north [49]. Topography and surficial deposits are two significant factors of fire risk because they influence the drying potential of the forest floor as well as fuel composition and structure [14,18,40]. Well-drained stands are more likely to burn [18], and the slopes found in the northern portion of the transect could, for example, help with draining and thus drying the forest floor, thereby facilitating fire spread.…”
Section: Climate Influence On Fire Riskmentioning
confidence: 99%
“…Fires also influence stands' composition by controlling succession patterns, for instance, by favoring fire-adapted species such as jack pine (Pinus banksiana) or black spruce (Picea mariana) [9][10][11]. Fire regimes are highly variable in space as a result of various environmental factors acting on different scales [12][13][14]. Climate acts as a top-down factor from regional to continental scales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation